Analisis Sentimen Aplikasi E-Government pada Google Play Menggunakan Algoritma Naïve Bayes - Artanti Inez Tanggraeni; Melkior N. N. Sitokdana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
E-gov is a digital innovation created by the government to create more effective and efficient business processes to meet the needs of the community. As a manifestation of this innovation in the land sector, the government makes an application called Sentuh Tanahku. Sentuh Tanahku is distributed on Google Play and generates a lot of reviews from users. The results of these reviews have an impact on the use and development of the application. However, with the large amount of review data, it will be difficult to process manually. Therefore, a method is needed to automatically see the user's tendency towards the application, whether it is positive or negative. The method that will be used is sentiment analysis. The stages are collecting review data on Google Play, manually labeling to get positive and negative review data, data preprocessing, TF-IDF weighting, classification using the Naïve Bayes algorithm, and evaluation. The labeling process shows that Sentuh Tanahku application gets positive response from users with a comparison of 407 positive reviews and 235 negative reviews. And from the results of sentiment analysis testing using the Naïve Bayes algorithm with TF-IDF weighting, it produces an accuracy of 89%, precision of 83%, and recall of 87%.